2019
DOI: 10.1111/1758-2229.12760
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of seed and rhizosphere microbial communities through plant–soil feedback and soil memory

Abstract: Summary Since the discovery of the role of microbes in the phytobiome, microbial communities (microbiota) have been identified and characterized based on host species, development, distribution, and condition. The microbiota in the plant rhizosphere is believed to have been established prior to seed germination and innate immune development. However, the microbiota in seeds has received little attention. Although our knowledge of the distribution of microbiota in plant seeds and rhizosphere is currently limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 57 publications
1
44
0
1
Order By: Relevance
“…Such initial seed-borne differences among the below-and aboveground plant tissues may cause strong priority effects during later development. Our demonstration of partial transmission of the seed microbiome to the roots con rms previous work suggesting that plant seeds are a repository for rhizosphere microbial communities [64], and the high resemblance of the embryonic and phyllosphere microbiome indicates that seeds may play an even larger role as a repository for the phyllosphere microbial community.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Such initial seed-borne differences among the below-and aboveground plant tissues may cause strong priority effects during later development. Our demonstration of partial transmission of the seed microbiome to the roots con rms previous work suggesting that plant seeds are a repository for rhizosphere microbial communities [64], and the high resemblance of the embryonic and phyllosphere microbiome indicates that seeds may play an even larger role as a repository for the phyllosphere microbial community.…”
Section: Discussionsupporting
confidence: 86%
“…We also hypothesized that the majority of seed-associated microbes would be transient and that only a small fraction of the microbial taxa would be transmitted to the developing seedling [13,26]. We lacked a strong prior on the subsequent distribution of the transmitted microbiome, but some studies have suggested that the composition of seed-associated microorganisms re ects the microbial community in the roots [4,28], while seed transmission to the phyllosphere is more limited [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…To date, many important questions regarding these associations remain unanswered, especially concerning the factors determining the community assemblage and diversity of the plant microbiome 3 . Increasing evidence suggests that plants can actively recruit a bene cial micro ora to facilitate their adaptation to environmental conditions and changes 3,6,7 . However, further studies are needed to generalize this hypothesis, and enable practical applications, especially for horticultural perennial crops grown in cultural conditions 8 .…”
mentioning
confidence: 99%
“…Although the underlying mechanisms are unclear, the rhizosphere microbiota has shown a resemblance to the seed-associated microbiota in the compositional structure (Nelson et al, 2018). Moreover, recent evidence has confirmed microbial migration between the seed and the rhizosphere, and the two compartments may serve as the microbial repositories for each other (Kong et al, 2019). A comparison between the seed and the rhizosphere microbiota of rice, therefore, would infer the fractional contribution of the two transmission routes to the assembly of indigenous microbiota of rice seeds, and potentially their association with rice development and health.…”
Section: Introductionmentioning
confidence: 99%